2011
DOI: 10.5751/es-04053-160203
|View full text |Cite
|
Sign up to set email alerts
|

Assessing an Adaptive Cycle in a Social System under External Pressure to Change: the Importance of Intergroup Relations in Recreational Fisheries Governance

Abstract: Assessing an adaptive cycle in a social system under external pressure to change: the importance of intergroup relations in recreational fisheries governance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
(63 reference statements)
0
28
0
3
Order By: Relevance
“…The reconstruction of the causal links between the different historical events in the region and outcomes in terms of the resilience of social-ecological systems was based on a considerable amount of sources and data that retain, however, a certain degree of subjectivity [28,29]. To deal with this, we have relied on the direct involvement of stakeholders.…”
Section: Materials Methods and Sources Of Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The reconstruction of the causal links between the different historical events in the region and outcomes in terms of the resilience of social-ecological systems was based on a considerable amount of sources and data that retain, however, a certain degree of subjectivity [28,29]. To deal with this, we have relied on the direct involvement of stakeholders.…”
Section: Materials Methods and Sources Of Informationmentioning
confidence: 99%
“…In another study, Nkhata et al [43] employed trust and commitment as proxies for potential, while they defined connectedness as the degree to which actors in social relationships are linked. Daedlow et al [29] attempted to develop in a social system indicators to differentiate potential and connectedness et al All three studies found that assessing the properties of potential and connectedness remained a challenge when applying the adaptive cycle and highlighted the need for the greater inclusion of disciplinary social science theories to describe transitions between various system stages in social systems.…”
Section: The Adaptive Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Certains chercheurs indiquent aussi qu'il est difficile de mesurer les dimensions du cycle d'adaptation (Carpenter et al 2001). D'autres suggèrent qu'il est nécessaire d'inclure davantage d'approches interdisciplinaires pour décrire les transitions entre les différentes étapes qui se succèdent au sein des systèmes socioécologiques (Abel et al 2006;Daedlow et al 2011;Davidson 2010;Gunderson et Holling 2002). Cela dit, nos entrevues démontrent que les participants à notre recherche sont à l'aise avec le concept de résilience et y voient plusieurs similarités avec les savoirs traditionnels.…”
Section: Discussionunclassified
“…This theory, while originating in biophysical processes, has been viewed increasingly as relevant to illuminating social processes (Daedlow, Beckmann, & Arlinghaus, 2011;Dooley, 1997; Ownership A conversation that begins with acknowledging how one has contributed to creating the current community reality. Subsequently this becomes a stance from which to initiate new action, rather than to assign blame.…”
Section: De-structuringmentioning
confidence: 99%